Characterization of Porosity and Thermal Properties of Ni-Doped Carbosils Obtained by Starch Gelation - Barbara Charmas (Adsorption Science & Technology)
This paper presents the studies of effects of different Ni 2+ contents on the structural and thermal properties of carbosils prepared by deposition of carbon matter (starch gelation) on the silica gel (Si-50) matrix. These mesoporous materials were characterized by a varied pore structure with developed surface and large pore volume. The porous structure of the initial silica gel and carbosils was characterized by the low-temperature nitrogen adsorption/desorption method as well as by pore-size distribution calculated from the calorimetric data by analyzing the thermal effects of liquid-phase transitions (water, n-decane and 1-decanol) confined in the pores of porous materials. The interfacial behaviour of different media confined incarbosil pores during the freezing/melting processes of obtained materials was studied. The results show that different catalyst contents have a significant effect on the porous structure formation.